2021
DOI: 10.1177/02692163211022957
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of a consult model versus an integrated palliative care and medical oncology co-rounding model on health care utilization in an acute hospital – an open-label stepped-wedge cluster-randomized trial

Abstract: Background: The benefit of specialist palliative care for cancer inpatients is established, but the best method to deliver specialist palliative care is unknown. Aim: To compare a consult model versus a co-rounding model; both provide the same content of specialist palliative care to individual patients but differ in the level of integration between palliative care and oncology clinicians. Design: An open-label, cluster-randomized trial with stepped-wedge design. The primary outcome was hospital length of stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…12,15,28 The SW-CRT of palliative care models that motivated this work did not include the unexposed cluster in its original analysis due to the lack of methodological guidance at the time. 32 In this article, we demonstrated that the inclusion of unexposed clusters in a fixed effects LSDV model is a viable strategy for improving the precision of the intervention effect estimate in a SW-CRT design. We mathematically proved this in Section 2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12,15,28 The SW-CRT of palliative care models that motivated this work did not include the unexposed cluster in its original analysis due to the lack of methodological guidance at the time. 32 In this article, we demonstrated that the inclusion of unexposed clusters in a fixed effects LSDV model is a viable strategy for improving the precision of the intervention effect estimate in a SW-CRT design. We mathematically proved this in Section 2.…”
Section: Discussionmentioning
confidence: 99%
“…Unexposed clusters (clusters never exposed to intervention) are seen in SW-CRTs in real-world research. 25,32 For example, SW-CRTs that are terminated early can result in clusters that are never exposed to intervention. SW-CRTs with unexposed clusters somewhat resemble the "optimal design" discussed by Thompson et al 36 and Girling and Hemming.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations